Patient Experience of Inpatient Care and Services Received at a Teaching Hospital in Malaysia: A Cross-Sectional Study - Wan Nawawi, Wan Nor Fatihah; Ramoo, Vimala; Chong, Mei Chan; Ahmad, Nor Zehan (UI Scholars Hub, 2022)
Background: Patients’ experience reflects the quality of healthcare services from the end user’s perspective and therefore is an essential indicator of healthcare quality. This study aimed to measure patient experience of inpatient care and services received at a teaching hospital. Methods: A total of 321 patients were enrolled in this quantitative, cross-sectional study during their discharge. Data were collected from May to September 2018 through a validated self-administered questionnaire adapted from the Hospital Consumer Assessment of Healthcare Providers and Systems survey. Analysis of patient experience and overall hospital quality rating was conducted using SPSS version 25. Results: The majority of the patients (91%) reported a positive experience of inpatient care and perceived a high quality of service provided by the hospital. Further analysis revealed that the patients’ experiences varied significantly with their age, ethnicity, religion, employment status, type of ward, and perceived health status (all p < 0.05). Meanwhile, the level of patient experience was significantly correlated with the overall rating of the hospital (r = 0.804, p < 0.001). Conclusions: The findings served as benchmark data for hospital management to address issues related to hospital services. Future studies should be extended to patients from multidisciplinary wards and outpatient units to provide a significant reflection of hospital service quality.